2007
DOI: 10.1165/rcmb.2006-0036oc
|View full text |Cite
|
Sign up to set email alerts
|

Contractility and Ca2+ Signaling of Smooth Muscle Cells in Different Generations of Mouse Airways

Abstract: The control and mechanisms of airway smooth muscle cell (SMC) contraction were investigated with a sequential series of lung slices from different generations of the same airway from the cardiac lobe of the mouse lung. Airway contraction was measured by monitoring the changes in airway lumen area with phase-contrast microscopy. Changes in intracellular calcium concentration of the SMCs were studied with a custom-built confocal or two-photon microscope. The distribution of the airway SMCs and the muscarinic Exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…In our study, no ventilation defect could be observed, but only homogeneous ventilation parameters decrease. This observation is in agreement with a more homogeneous distribution of serotonin receptors throughout the airway generations (18), whereas intravenous injection of methacholine predominantly elicits central airway obstruction (19) in relation to a higher presence of muscarinic M3 receptors in middle or proximal airways (18).…”
Section: Discussionsupporting
confidence: 85%
“…In our study, no ventilation defect could be observed, but only homogeneous ventilation parameters decrease. This observation is in agreement with a more homogeneous distribution of serotonin receptors throughout the airway generations (18), whereas intravenous injection of methacholine predominantly elicits central airway obstruction (19) in relation to a higher presence of muscarinic M3 receptors in middle or proximal airways (18).…”
Section: Discussionsupporting
confidence: 85%
“…In previous experiments, we (2) established that the responsiveness of mouse airway SMCs varied in different airway generations and that the sensitivity of the relationship between contraction and Ca 2ϩ oscillations was decreased in larger airways. Because we have compared similar-sized airways from rat and mice, it is possible that the difference we observe between similar-sized mouse and rat airways is the result of a comparison of airways from different airway generations.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, the idea that hyperresponsiveness is associated with a structural difference assumes that the underlying Ca 2ϩ -dependent signaling mechanisms in each SMC remains identical. However, our investigations have revealed that the extent of airway contraction varies at different airway locations and that this correlates with different frequencies of Ca 2ϩ oscillations within SMCs (2). Consequently, the focus of this study was to determine the importance of the contribution of the Ca 2ϩ signaling and Ca 2ϩ sensitivity to airway SMCs contractility by comparing these two processes in rats and mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BAI et al [21] have shown that the magnitudes of constrictor responses in lung slices vary over a very wide range of airway sizes; however, they did not include contraction/relaxation velocities in those comparisons. In the present study, in which a much smaller range of airway sizes was examined, neither the magnitudes nor the velocities of contraction were found to correlate in a statistically significant manner with airway size ( fig.…”
Section: Validation Of the Experimental Approachmentioning
confidence: 99%